Pelatihan dan Pendampingan terhadap Penerapan K3 pada Pekerja Konstruksi Skala Kecil di Kota Semarang - Widiatmoko, Kukuh Wisnuaji; Billahi, Bagus Acung; Mahmud, Faizal; Masvika, Hendra (Jurnal Pengabdian KOLABORATIF, 2025)
The implementation of Occupational Safety and Health (OSH) in small-scale construction projects remains a serious challenge, particularly in Semarang City. Workers in this sector generally do not have an adequate understanding of the importance of using Personal Protective Equipment (PPE) in supporting occupational safety. This community service activity aims to provide direct training and mentoring to small-scale construction workers to understand and apply OSH in their daily work activities. The implementation method involves an initial survey through interviews and field observations, followed by participatory training and mentoring in the practice of using PPE. The results of the activity show that after the training, workers' understanding and compliance with the use of PPE increased from 50% to 80%. However, some workers still require further mentoring to get used to implementing OSH consistently. This program is felt to have a positive impact in raising awareness that occupational safety is not just a formal obligation. Still, a basic need that protects oneself, is reflected in the results of the post-test questionnaire that 90% of participants expressed their desire to comply with and implement the OSH program.
Keywords: construction worker; occupational safety and health; small scale construction; personal protective equipment